Correction: Exploring the impact of trait number and type on functional diversity metrics in real-world ecosystems. - Timothy Ohlert; Kaitlin Kimmel; Meghan Avolio; Cynthia Chang; Elisabeth Forrestel; Benjamin Gerstner; Sarah E Hobbie; Kimberly Komatsu; Peter Reich; Kenneth Whitney (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0272791.].